Vowel Production in Aphasia: Preliminary Acoustic Findings from Arabic - Hisham, Adam (East European Journal of Psycholinguistics, 2021)
The present study examined the temporal and spectral characteristics of vowels produced by Palestinian Arabic- speaking individuals with Broca’s aphasia compared to healthy speakers. Specifically, vowel duration and formant frequency measures (F1&F2) were made. eight speakers with Broca’s aphasia and eight healthy speakers participated in the study. Repetition was used to elicit the target vowels to minimize language comprehension or reading difficulties by the individuals with Broca’s aphasia. The speech sample contains the long vowels (/a:,u:,i:/) embedded in CVC words with nasal initials. Statistical analysis was used to determine any significant differences concerning the formant values (F1/F2) between the speaker groups. Findings showed that speakers with Broca’s aphasia produced vowel categories with more variability than healthy speakers. For some, formant frequencies were comparable with those of the healthy speakers, and yet others showed an overlap of phonetic categories. Specifically, F1 and F2 for the vowel /u:/ were higher for individuals with Broca’s aphasia compared to normal-speaking individuals, but they were not statistically significant. Furthermore, although speakers with Broca’s aphasia produced longer vowel durations than the healthy speakers, they were not significantly different between speaker groups except for the vowel /i:/. Reduced vowel space was also observed in speakers with Broca’s aphasia. The vowel ellipses as shown by speakers with Broca’s aphasia were larger than those of healthy speakers. Results support previous studies showing abnormal temporal durations and spectral patterns in Broca’s aphasia. Findings can contribute to cross-linguistic research on vowel production in aphasia, mainly in understudied languages such as Arabic.